Heterotic potential, potence ratio, combining ability and genetic control of seed vigour traits for yield improvement in cucumber (Cucumis sativus) - KUMAR, SANDEEP; KUMAR, RAMESH; DOGRA, RAJESH KUMAR (The Indian Journal of Agricultural Sciences, 2018)
The paucity of research on seed quality enhancement for yield improvement in cucumber (Cucumis sativus L.) motivated us to undertake this study. Therefore, present investigation was carried out to estimate the combining ability, gene action, heterosis and potence ratio for seed vigour and yield traits in 48 F1 crosses, developed by crossing 16 lines (8 gynoecious) and 3 testers during the year 2011. The seeds of all parents and their crosses, along with two standard checks (KH-1 and Pusa Sanyog), were assessed for different seed vigour (under laboratory conditions) and fruit yield (under open field conditions) traits during the year 2012. Experimental results revealed that parental lines LC-1-1, CGN-20953 and LC-3-3 were found superior on the basis of mean performance and general combining ability studies. Four cross combinations, viz., LC-1-1 × K-75, CGN-20953 × Poinsette, LC-3-3 × Poinsette and LC-3-3 × K-75 were found best on the basis of mean performance, specific combining ability and heterosis studies. Further, results of potence ratio reflected partial dominance for different seed vigour traits in all top five heterotic hybrids, while over dominance was exhibited by all the heterotic hybrids towards higher fruit yield per ha in cucumber. Gene action studies indicated the predominant role of non-additive gene action for the control of all the traits under study; hence heterosis breeding can be utilized for the genetic improvement of seed vigour and fruit yield traits in cucumber.